Composição florística, estrutura fitossociológica e caracterização sucessional de três fragmentos florestais, na Estância Turística de Itu - SP, Brasil - Wakabayashi, Tatiana Yukari (2015)
The city of Itu has only 9.90% of its territory with native vegetation. Knowledge of native vegetation and biodiversity with studies of the floristic composition and phytosociological structure of the remaining forests are important for understanding the structure and dynamics of these formations. This study aimed to analyze the floristic composition, structure and successional stage of three remaining semideciduous forest located in the city of Itu. And with these results, discuss the possible influences of size, land tenure (private or public), land use in their surroundings and protected areas, in addition to verifying the presence of endangered species. The points were named: Pesqueiro, Cidade Nova and Fazenda. At each point, was allocated 12 plots of 10m X 10m and identified individuals with circumference at breast height (CAP) equal to or greater than 15 cm. The phytosociological parameters were calculated by FITOPAC 2.1 software being sampled 552 individuals distributed into 149 species considering the total area (0.36 ha), and Shannon-Wiener diversity index (H?) estimated in 4.46. The five richest families were Myrtaceae (19 species), Fabaceae (19), Lauraceae (12), Euphorbiaceae (9) and Rubiaceae (8). The ten species with the highest IVI, in general, showed characteristic of advanced stage of succession. From 552 individuals, 73% are not pioneers and 16% are pioneers. Through correspondence and cluster analysis, it observed the formation of three major groups which coincide with the sampled points, even with low similarity values. This low similarity is shown in the Venn diagram and Jaccard similarity index (Ij) between points, the maximum value of Ij occurred between Pesqueiro and Fazenda points (13.8%). Species were sampled on all points with some degree of threat according to the lists consulted, they are: Myrceugenia campestris, Machaerium villosum, Brosimum glaziovii, Myrcianthes pungens and Cedrela fissilis. Comparing the diversity indexes, the Fazenda Point had the highest value with H? = 3.88, followed by Pesqueiro Point with H? = 3.63 and Cidade Nova point with H? = 3.47. It was observed greatest richness in Pesqueiro Point (69 species), followed by Fazenda Point (68) and finally Cidade Nova point (51). The size of the area did not affect the species richness, because different fragment sizes showed similar number of species. Cidade Nova point, placed in public property with urban surroundings, showed important to preservation of urban green areas and can act as stepping stones. As for the Pesqueiro and Fazenda points, placed in private property with rural surroundings are important in connectivity between fragments inserted in this landscape. Cidade Nova and Fazenda points are included in protected areas (APA), but there are no guarantees of maintenance of the quality of these fragments. The same can happen for the Pesqueiro point, which could suffer serious impact. This study indicated that each fragment has a series of characteristics, which emphasizes their uniqueness and importance in view of conservation.